The Influence of Problem Based Learning (PBL) Model on Students' Mathematical Problem Solving Ability in Elementary Schools - Ajeng Julia; Erna Suwangsih; Puji Rahayu (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2025)
The background of this research problem is due to the low mathematical problem-solving ability of elementary school students, students find it difficult to understand the material taught. The purpose of this study is to determine the influence and improvement of the Problem Based Learning (PBL) model on students' mathematical problem-solving abilities in elementary school. This type of research uses a quasi-experiment with a nonequivalent control group design model. The sample in this study uses a purpossive sampling technique, with two classes as samples. For the experimental class, the VB class gets the Problem Based Learning (PBL) treatment model while the VA class gets the conventional treatment model. The instrument used in this study is in the form of four descriptive questions to measure students' mathematical problem-solving skills. The results showed that the improvement of mathematical problem-solving skills of VB class students who used the Problem Based Learning (PBL) model got better results than VA class students who used the conventional model. The Problem Based Learning (PBL) model has an effect of 68.2% on students' mathematical problem-solving skills. Judging from the results obtained, the Problem Based Learning (PBL) learning model can be used as an alternative to teaching and learning activities in the classroom so that the learning carried out becomes more active and trains students' mathematical problem-solving skills.